Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5056/jnm19042
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolites in Irritable Bowel Syndrome: An Overnight Time-course Study

Abstract: Background/AimsPatients with irritable bowel syndrome (IBS) often report poor sleep quality. Whether poor sleep is associated with tryptophan (Trp) metabolites is unknown. We compared serum Trp metabolites in women with IBS and healthy controls (HCs) using targeted liquid chromatography mass spectrometry (LC-MS)-based profiling. In IBS only, we explored whether Trp metabolites are associated with IBS symptoms and subjective and objective sleep indices, serum cortisol, plasma adrenocorticotropic hormone (ACTH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Further studies are needed on the role of threonine in IBS‐D. Tryptophan, which is converted to serotonin, is known to be associated with IBS, as the increased serotonin levels lead to increased GI motility and visceral hypersensitivity . Previous studies have shown that patients with IBS‐D have comparatively higher levels of free serum tryptophan than those in HC .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed on the role of threonine in IBS‐D. Tryptophan, which is converted to serotonin, is known to be associated with IBS, as the increased serotonin levels lead to increased GI motility and visceral hypersensitivity . Previous studies have shown that patients with IBS‐D have comparatively higher levels of free serum tryptophan than those in HC .…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be an indirect effect of sleep problems on abdominal pain through daytime dysfunction in adults with irritable bowel syndrome, 83 furthermore the pineal gland circadian hormone melatonin levels were positively associated with decreased abdominal pain in IBS. 84 In a systematic review of exogenous supplementation of melatonin, all the small studies with significant heterogeneity, and low-quality evidence (Table 1) consistently showed improvement in abdominal pain for IBS. 85 Daytime sleepiness was the only side effect in some patients.…”
Section: Le Ss Well-e Viden Ced Current Approache S To Ibs Pain Tre Atmentmentioning
confidence: 99%
“…Poor sleep quality, including frequent awakenings, fatigue, and not feeling rested in the morning are symptoms commonly reported by women with IBS. Given the evidence that serotonin, the most well-known tryptophan metabolite, is involved in pain sensitivity, gut motility, gut function, and secretion (Costedio et al, 2007) and the common thinking that tryptophan is a precursor to melatonin, Dr Heitkemper conducted a targeted metabolomics study investigating the role of tryptophan metabolites in IBS symptoms and explored the association of these metabolites to sleep measures (Burr et al, 2019).…”
Section: Targeted Metabolomics Use In Researchmentioning
confidence: 99%
“…Using nocturnal blood samples collected from both IBS and healthy control subjects exposed to a social stressor, Heitkemper’s findings suggest that with the exception of nicotinamide, tryptophan metabolites decreased across the night in both controls and women with IBS (Burr et al, 2019). She also identified that compared to the control group, nicotinamide levels were higher and indole-3-lactic acid levels lower in the IBS group (Burr et al, 2019).…”
Section: Targeted Metabolomics Use In Researchmentioning
confidence: 99%
See 1 more Smart Citation